A Recurrent Central Giant Cell Granuloma in a Young Patient and Orthodontic Treatment: A Case Report. (December 2016) - Patel, Devaki; Minhas, Gursharan; Johnson, Paul
Central giant cell granuloma (CGCG) is an uncommon benign intraosseous lesion of the jaw, found predominantly in children and young adults below 30 years of age. The purpose of this article was to present a summary of the current literature and a case report of an 11-year-old boy diagnosed with an aggressive CGCG involving the anterior maxilla that was removed in 2004 and subsequently recurred almost 3 years later in 2006. The presenting features of the patient and the effect of combined surgical and orthodontic treatment for this condition are discussed. This case shows how the dentition was successfully maintained with conservative surgery and orthodontic treatment in spite of the extensive destruction of the supporting bone, and the importance of long-term follow-up. The report also reminds orthodontic practitioners that rare pathological conditions can occur in their child patient groups.